The Sustainable Prescription: Benefits of Green Roof Implementation for Urban Hospitals - O'Hara, Aprelle C.; Miller, Amelia Christine; Spinks, Hailey; Seifert, Alexandria; Mills, Tirzah; Tuininga, Amy R. (Frontiers in Sustainable Cities, 2022)
If worldwide healthcare was a country, it would be the fifth largest emitter of greenhouse gases on the planet. The increase in global temperatures, combined with the negative impacts of urbanization, has made it more important than ever to introduce green spaces where possible. With climate change worsening, human health, both physically and mentally is on decline, making the effects of climate change especially pressing to the stability of healthcare systems. In order to mitigate the lasting impacts of climate change on healthcare facilities, a holistic solution is needed. Access to green space in hospitals has been shown to reduce emotional distress, improve mental health, increase socialization and community connection, increase physical activity, decrease cardiovascular and respiratory diseases, decrease pain management needs and hospital stay lengths and increase both patients' and staffs' overall satisfaction at the facility. Beyond benefiting those interacting with the hospital, green roofs have the ability to reduce the urban heat island effect, improve stormwater mitigation, increase biodiversity, and absorb toxins and pollutants through air filtration. Additionally, green roofs can offer lower maintenance costs and higher energy savings than traditional roofs, and improve patient satisfaction, which can result in future funding opportunities. However, the upfront and upkeep costs of installing a green roof can vary and must be considered before implementation. In this review, we explore the symbiotic relationship between urban green roofs and hospital/patient wellness through the lens of sustainability, which includes environmental, societal, and economic impacts. We review scientific journal articles investigating benefits of green space and green roofs and highlight examples of green roofs on hospitals in the United States; together, these approaches display the environmental, societal, and economic benefits of green roofs installed on healthcare facilities. This review offers insight to hospitals, decision makers, and government systems on the importance of green roofs in urban areas and how these infrastructures can support the economic growth of the institute. Using our framework, decision makers and planners for urban hospitals can evaluate how the addition of green roofs to their healthcare facilities can contribute to increased environmental resiliency, community health, and patient satisfaction.